Teachers’ attitudes to cultural diversity: Results from a qualitative study in Russia and Taiwan - Wang, Jui-Sheng; Lan, Jesse Yu-Chen; Khairutdinova, Rezeda R.; Gromova, Chulpan R. (Frontiers in Psychology, 2022)
This study examined elementary school teachers' attitudes toward immigrant students and their families in Russia and Taiwan. Qualitative methodology was used for data collection. Teachers' attitudes and conceptual orientations toward cultural diversity in the classroom were identified. Teachers' attitudes were categorized into three groups: Attitudes toward children, parents, and diverse ethnic groups. The results showed that teachers had positive attitudes toward children with immigrant backgrounds and ambivalent attitudes toward their parents. The results showed that attitudes toward cultural diversity influence teachers' expectations of immigrant students' academic achievement and classroom teaching methods. The results indicate that greater levels of cross-cultural contact lead to a more tolerant approach by teachers in their classrooms.